Translation Method of English Hymn Song into Indonesian Version in Kidung Jemaat - Lola Purba; Winda Setiasari (Universitas Negeri Medan, 2022)
This study aimed to find out what, how, and why the translation methods became the most dominant in translating English Hymn song in kidung jemaat. This study used a descriptive qualitative approach. The data of this study were 22 songs lyrics by E.L.Pohan. The source of the data was taken from kidung jemaat Hymn song book. The result of this study showed that there are three types of methods used in translating English Hymn song lyrics in to Indonesian language. The most dominant used by the translator is the Adaptation method (68,18%). The adaptation method is the most dominantly used by the translator because it retains the meaning contained in the SL, even though the words are substituted to fit the culture and rythmic calculation of each lyrics word, without altering the original meaning.